The impact of government subsidies and enterprises' R&D investment: A panel data study from renewable energy in China. (February 2016) - Yu, Feifei; Guo, Yue; Le-Nguyen, Khuong; Barnes, Stuart J.; Zhang, Weiting
Abstract: In this research, we aim to understand the influence of government subsidies on enterprises' research and development (R&D) investment behavior, particularly in China's renewable energy sector. We are also interested in examining how the attributes of enterprise ownership act as a moderating variable for the relationship between government subsidies and R&D investment behavior. Three classical panel data analysis models including the pooled ordinary least squares (OLS) model, the fixed effect model and the random effect model are employed. We find that government subsidies have a significant crowding out influence on enterprises' R&D investment behavior and that the influence is further moderated by the attributes of enterprise ownership. Moreover, a panel threshold regression model is used to demonstrate how the influence of government subsidies on enterprises' R&D investment behavior will change when government subsidies increase. Two thresholds, 0.6% and 10.1%, are identified. We recommend that relevant government departments should motivate enterprise R&D investment behavioral intention by increasing subsidies within a certain range. Different attributes of enterprise ownership should also be considered as part of policy reform and re-structuring relating to government subsidies. Highlights: Government subsidies have a significant crowding-out effect on enterprises' R&D. The moderating role of the attributes of company ownership is examined. A panel threshold regression model is used to explore the influence of subsidy. First examining the effect of subsidy in the renewable industry in China.